The Effectiveness of the Colorful Balls Run Games Model on Improving the Short-Distance Running Learning Outcomes of Phase C Elementary School Students - Septian Raibowo; Fadhlil Hadi; Aldino Aldino; Meliana Meliana (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study aimed to develop and examine the effectiveness of the Colorful Balls Run Games learning model in improving short-distance running skills among Phase C students at SDN 106 Kota Bengkulu. The research employed a Research and Development (R&D) approach consisting of four main stages: preliminary study, model design, limited trial, and product revision. The participants were 24 elementary students (13 boys and 11 girls). A one-group pretest–posttest design was applied using a 40-meter sprint test, observation sheets, and teacher evaluations as instruments. The findings indicated a significant improvement in sprint performance, with the average running time decreasing from 10.27 seconds to 9.35 seconds (p < 0.05). Additionally, students’ motivation and active participation increased from 63% to 91%. The Colorful Balls Run Games model effectively created an enjoyable learning atmosphere, fostered enthusiasm, and enhanced students’ fundamental motor skills. This model can be recommended as an innovative instructional approach for short-distance running lessons in elementary physical education